Management and 5-year outcome of patients with coronary artery disease in different periods of stent technology. Issue 6 (June 2020) - Olivari, Zoran; Stritoni, Paolo; Burelli, Claudio; McMahon, Laura; Capodaglio, Giulia; Fedeli, Ugo; Avossa, Francesco; De Servi, Stefano; Favero, Luca
Abstract : Background: The availability of bare metal stents (BMS) followed by drug-eluting stents of first- (DES1) and second-generation (DES2) progressively increased the rate of the percutaneous revascularizations [percutaneous coronary intervention (PCI)] with unknown impact on the long-term outcome of real-world patients with established coronary artery disease. We sought to investigate treatments applied in patients with coronary artery disease in BMS, DES1 and DES2 eras and their 5-year outcome. Methods: A total of 3099 consecutive patients with at least one coronary stenosis more than 50% observed in 2002 (BMS era), 2005 (DES1 era) and 2011(DES2 era) were enrolled at 13 hospitals in Veneto region, Italy. Results: Moving from BMS to DES1 and DES2 eras patients became significantly older, had more comorbidities and received more frequently statins, betablockers, renin–angiotensin modulators and antiplatelets ( P  < 0.0001 for all). The PCI/conservative therapy ratio increased from 1.9 to 2.2 and 2.3, the PCI/coronary artery by-pass surgery ratio from 3.6 to 4.0 and 5.1. The crude 5-year survival was 84.9, 83.4 and 81.4% ( P  = 0.20) and survival free of myocardial infarction, stroke or further revascularizations was 62.1, 60.2 and 60.1% ( P  = 0.68), with cardiovascular mortality accounting for 60.9, 55.6 and 43.4% of deaths. At multivariable analysis cardiovascular mortality was significantly lower in patients enrolled in 2011 vs. 2002 (hazard ratio = 0.712, 95% confidence interval 0.508–0.998, P  = 0.048). Conclusion: From BMS to DES1 and DES2 eras progressive worsening of patients characteristics, improvement of medical treatment standards and increase in PCI/conservative therapy and PCI/coronary artery by-pass surgery ratios were observed. Five-year outcomes remained similar in the three cohorts, but in the DES2 era cardiovascular mortality was reduced. Abstract : Supplemental Digital Content is available in the text